After Christianity - Vattimo, Gianni, 1936- (Italian Academy lectures., 2002)
What has been the fate of Christianity since Nietzsche's famous announcement of the ""death of God""? What is the possibility of religion, specifically Christianity, thriving in our postmodern era? In this provocative new book, Gianni Vattimo, leading Italian philosopher, politician, and framer of the European constitution, addresses these critical questions. When Vattimo was asked by a former teacher if he still believed in God, his reply was, ""Well, I believe that I believe."" This paradoxical declaration of faith serves as the foundation for a brilliant exposition on Christiani.